2021
DOI: 10.1016/j.vaccine.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Within-country age-based prioritisation, global allocation, and public health impact of a vaccine against SARS-CoV-2: A mathematical modelling analysis

Abstract: The worldwide endeavour to develop safe and effective COVID-19 vaccines has been extraordinary, and vaccination is now underway in many countries. However, the doses available in 2021 are likely to be limited. We extended a mathematical model of SARS-CoV-2 transmission across different country settings to evaluate the public health impact of potential vaccines using WHO-developed target product profiles. We identified optimal vaccine allocation strategies within- and between-countries to maximise averted death… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 49 publications
3
70
0
Order By: Relevance
“…Given low vaccine efficacy, low coverage, or sustained transmission, prioritizing individuals >60 years of age should lead to the greatest reductions in hospitalisations and mortality (37) , while targeting younger individuals should lead to the greatest reduction in incidence (14) . However, clear thresholds for vaccine efficacy and population-level coverage were identified, beyond which (e.g., when vaccine supply increases) a suppression strategy that targets middle-aged (30–59) transmitters becomes optimal across all optimisation targets (e.g., incidence, hospitalisations, and deaths) [13] , [38] . Because human contact patterns are heterogeneous but broadly understood, targeted strategies are likely to be far more effective at reducing disease burden than indiscriminate vaccination campaigns, whether targeting is directed according to age (14) , occupation (e.g.…”
Section: Optimising Vaccine Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given low vaccine efficacy, low coverage, or sustained transmission, prioritizing individuals >60 years of age should lead to the greatest reductions in hospitalisations and mortality (37) , while targeting younger individuals should lead to the greatest reduction in incidence (14) . However, clear thresholds for vaccine efficacy and population-level coverage were identified, beyond which (e.g., when vaccine supply increases) a suppression strategy that targets middle-aged (30–59) transmitters becomes optimal across all optimisation targets (e.g., incidence, hospitalisations, and deaths) [13] , [38] . Because human contact patterns are heterogeneous but broadly understood, targeted strategies are likely to be far more effective at reducing disease burden than indiscriminate vaccination campaigns, whether targeting is directed according to age (14) , occupation (e.g.…”
Section: Optimising Vaccine Distributionmentioning
confidence: 99%
“…essential-workers; 29), or those with higher degrees of social connectivity (40) . Similarly, at the global level, several modelling studies have found that allocating available doses in proportion to each country’s population size (compared to the current practices favouring high-income countries) is close to the optimal strategy (13) and could double the global number of deaths averted (41) . Further, initially distributing single doses (for two dose vaccines) should avert more deaths than providing fewer people with two doses, provided that protection conferred by a single dose is sufficiently high [12] , [42] .…”
Section: Optimising Vaccine Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted June 21, 2021. ; https://doi.org/10.1101/2021.06. 18.21259164 doi: medRxiv preprint cination would yield the largest reductions in mortality [3,4] given the steep gradient of mortality observed with age in China, Europe, and other countries [5,6]. Meanwhile, HCW have been prioritized to preserve health system capacity [2].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous mathematical models aiming to identify the best vaccination strategy 7,8,9,10,11,12,13,14,15,16 . Early models focused on reducing the spread of the infection and identifying priority groups for receiving the first dose.…”
Section: Introductionmentioning
confidence: 99%